KEWARISAN BEDA AGAMA DALAM PERSPEKTIF MAQĀSID SYARĪ’AH - Jayusman, Jayusman; Fahimah, Iim; Hidayat, Rahmat (Ijtimaiyya: Jurnal Pengembangan Masyarakat Islam, 2020)
This paper specifically discusses about religious differences as one of the barriers in inheritance. A Muslim does not inherit an infidel (kâfir), and conversely they also do not inherit a Muslim. Can a Muslim child inherit his infidel parents? In order to analyze this problem the author uses maqāsid syarī'ah review, where the law is determined for the benefit. This research concludes that it is permissible for a Muslim child to inherit his infidel parents, which is included in hifz al-dīn (maintaining religion) at the darūriyat level. This is because when a Muslim child is prohibited from inheriting his infidel parents, it is feared that his faith will waver, due to property problems. In the case of hifz al-māl, the hājiyat position, if a Muslim is prohibited from inheriting non-Muslim property, it means that any property that should be used for the benefit of the ummah will be lost.